Microwave-assisted extraction based on emulsion breaking with natural deep eutectic solvent for vegetable oil sample preparation prior to elemental determination by ICP OES - Costa, Floriatan Santos; Moreira, Luana Santos; Ludovico, Letícia Lima; Volpe, Jaqueline; de Oliveira, Ana Claudia; dos Santos, Mayara Padovan; da Silva, Erik Galvão Paranhos; Souto, Dênio Emanuel Pires; Grassi, Marco Tadeu; Gonzalez, Mario Henrique [UNESP]; Amaral, Clarice D.B. (Elsevier, 2024)
This study presents a novel and efficient method for the extraction of Al, Ca, Cr, Cu, K, Mg, Mn, and Zn in vegetable oil samples using a Natural Deep Eutectic Solvent (NADES) as an extractor combined with microwave radiation (MW) in an emulsion system. The NADES prepared with choline chloride:oxalic acid:water (1:1:4 molar ratio) provided a high extraction rate using 5.0 mL of the sample, 1.7 mL of NADES, and 1.3 mL of Triton X-100. The optimum conditions were obtained with 36 s of vortexing, 5 min of extraction, and 10 s for emulsion-breaking in MW. Under these conditions, recoveries ranged from 91% to 110% and relative standard deviations <9.0% were obtained. The limit of quantification (mg kg−1) was: 0.018 (Al), 0.032 (Ca), 0.007 (Cr), 0.006 (Cu), 0.013 (K), 0.027 (Mg), 0.002 (Mn), and 0.019 (Zn). The proposed method showed comparable results to reference methods and advantages, such as speed, low cost, and simplicity. The combination of NADES and MW represents a sustainable and innovative approach to the elemental determination composition of vegetable oils and contributes to advances in sample preparation methods.
Keywords: Eco-friendly solvent; Edible oil; Emulsion breaking; Experimental design; Food composition; Natural deep eutectic solvent